Correlation Between Changes in NLR Value and RECIST among Lung Cancer Patients at Saiful Anwar Malang Hospital - Kristianto, Fransiskus; Setyawan, Ungky Agus; Erawati, Dini Rachma (Respiratory Science, 2024)
Background: In practice, clinicians use Response Evaluation Criteria in Solid Tumors (RECIST) to decide the progressivity of lung tumors. Besides RECIST, there is an inflammatory marker called Neutrophil to Lymphocyte Ratio (NLR), which has prognostic value in cancer patients. Many previous studies have shown that NLR can predict the prognosis because inflammation in cancer patients is part of the tumor progressivity.  Therefore, the changes in NLR value have the potency to be one of the ways to decide the progressivity of tumors in lung cancer patients. Method: This cross-sectional study was conducted to see whether there is a correlation between RECIST and NLR in 95 lung cancer patients at Saiful Anwar Hospital whose data were taken from January 2022 to May 2023. The variable will be tested using the chi-square test to see the correlation and the logistic regression method to obtain the odds ratio. Results: There is a significant correlation between changes in NLR and RECIST with P=0.041.  Through Logistic Regression Analysis, the value of the odds ratio is 2.46 (CI 95%=1.03-5.94).  In the group with progressive RECIST, the average NLR value after therapy was higher than the average NLR value after therapy in the non-progressive group. Conclusion: This study concludes that changes in NLR value have the potency to help the determination process of lung cancer progressivity as RECIST does.